Analysis of the influence of digital marketing and brand image on the sales conversion rate of Shopee at PT Radysa Dharma Abadi in Medan City - Annisa Aulia Siregar; Zulkarnain Siregar (EDUCTUM: Journal Research, 2025)
This study aims to determine the effect of Digital Marketing and Brand Image on the sales conversion rate at Shopee PT. Radysa Dharma Abadi. This study uses a quantitative descriptive approach with multiple linear regression analysis techniques. Data analysis uses the SPSS version 22.0 program. The results of the analysis show that the variables of Digital Marketing and Brand Image have a positive and significant effect on the Sales Conversion Rate of Shopee at PT. Radysa Dharma Abadi. This is indicated by the Digital Marketing variable with a t-count value of 10,000, > t-table of 1.969, and a significant value of 0.000 <? (0.05). Meanwhile, the Brand Image variable also has a positive and significant effect on the Sales Conversion Rate of Shopee at PT. Radysa Dharma Abadi, with a t-count value of 5.798, t-table of 1.969, and a significance of 0.000 <? (0.05). Simultaneously, the results of the F test show that the Sig F value (0.000) < ? (0.05) and F count of 576.152 > F table of 3.03, which means that Digital Marketing and Brand Image together have a significant effect on the Shopee Sales Conversion Rate at PT. Radysa Dharma Abadi.